Dynamic PET Imaging Using Dual Texture Features - Ouyang, Zhanglei; Zhao, Shujun; Cheng, Zhaoping; Duan, Yanhua; Chen, Zixiang; Zhang, Na; Liang, Dong; Hu, Zhanli (Frontiers in Computational Neuroscience, 2022)
Purpose: This study aims to explore the effect of texture features on dynamic imaging of total-body positron emission tomography. Methods: We have improved a reconstruction method that combines radiological dual texture features. In this method, multiple short time frames are added to obtain composite frames, and the image reconstructed by composite frames is used as the prior image. We extract texture features from prior images using the gray level-gradient cooccurrence matrix (GGCM) and gray-level run length matrix (GLRLM). The prior information contains the intensity of the prior image, the inverse difference moment of the GGCM and the long-run low gray-level emphasis of the GLRLM. Results: The computer simulation results show that, compared with the traditional maximum likelihood, the proposed method obtains a higher signal-to-noise ratio (SNR) in the image obtained by dynamic PET reconstruction. Compared with similar methods, the proposed algorithm has a better NMSE and contrast recovery coefficient (CRC) at the tumor in the reconstructed image. Simulation studies on clinical patient images show that this method is also more accurate for the reconstruction of high-uptake lesions. Conclusion: The image obtained by using texture features in dynamic imaging of total-body positron emission tomography is more accurate at the tumor.